2004
DOI: 10.1016/s0886-3350(03)00584-4
|View full text |Cite
|
Sign up to set email alerts
|

Posterior capsule rupture and vitreous loss during phacoemulsification with or without the use of an anterior chamber maintainer

Abstract: The use of an ACM in phacoemulsification provided a consistently deep anterior chamber and approximately the same rate of complications as with a standard technique in the hands of experienced surgeons. However, when posterior capsule rupture occurred, the incidence of vitreous loss was significantly higher in eyes with an ACM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…4 Reported vitreous loss rates during cataract surgery in large cohorts of patients taking tamsulosin and patients not taking tamsulosin patients vary between 0.2% and 4.4%. [36][37][38][39][40][41][42][43][44][45][46][47][48][49] Anecdotally, 77% of the ASCRS IFIS survey respondents said they believe that the use of tamsulosin by cataract extraction patients increases the risk for cataract surgery complications compared with the risk when the patient is not taking the drug. 14 Given the intraoperative phenomena characteristic of IFIS, tamsulosin-associated cataract extractions may present a unique challenge to resident physicians; this challenge underscores the need for close supervision and careful surgical instruction during residency training.…”
Section: Discussionmentioning
confidence: 99%
“…4 Reported vitreous loss rates during cataract surgery in large cohorts of patients taking tamsulosin and patients not taking tamsulosin patients vary between 0.2% and 4.4%. [36][37][38][39][40][41][42][43][44][45][46][47][48][49] Anecdotally, 77% of the ASCRS IFIS survey respondents said they believe that the use of tamsulosin by cataract extraction patients increases the risk for cataract surgery complications compared with the risk when the patient is not taking the drug. 14 Given the intraoperative phenomena characteristic of IFIS, tamsulosin-associated cataract extractions may present a unique challenge to resident physicians; this challenge underscores the need for close supervision and careful surgical instruction during residency training.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, Androuid et al found that although ACMs maintained anterior chamber depth during PE, there was no reduction in complication rates, and patients in whom an ACM was used had greater vitreous loss in the event of posterior capsule rupture. 24 In this study, the ACM bottle was positioned at the same height as the irrigation fluid for the PE device throughout the operation. We detected no clinically significant IOP elevation in our patients postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…The ACM (the cost is US $ 10) has been used in cataract surgery, either in manual small incision cataract surgery or in phacoemulsification. [3][4][5][6] There is limitation of Simcoe's cannula and vitrector in this procedure. Both Simcoe's cannula and vitrector have relatively small "mouths" so that they create problems in removing bulky and springy fibrin in the AC.…”
Section: Discussionmentioning
confidence: 99%